Naturally-occurring altered peptide ligands control Salmonella-specific CD4(+) T cell proliferation, IFN-γ production, and protective potency - Johanns, Tanner M. (2009)
T cell activation required for host defense against infection is an intricately regulated and precisely controlled process. Although in vitro studies indicate three distinct stimulatory signals are required for T cell activation, the precise contribution of each signal in regulating T cell proliferation and differentiation after in vivo infection is unknown. In this study, altered peptide ligands (APLs) derived from the protective Salmonella-specific FliC antigen and CD4(+) T cells specific for the immune-dominant FliC(431–439) peptide within this antigen were used to determine how changes in TCR stimulation impact CD4(+) T cell proliferation, differentiation, and protective potency. To explore the prevalence and potential use of altered TCR stimulation by bacterial pathogens, naturally-occurring APLs containing single amino acid substitutions in putative TCR contact residues within the FliC(431–439) peptide were identified and used for stimulation under both non-infection and infection conditions. Based on this analysis, naturally-occurring APLs that prime proliferation of FliC-specific CD4(+) T cells either more potently or less potently compared with the wild-type FliC(431–439) peptide were identified. Remarkably, despite these differences in proliferation, all APLs primed reduced IFN-γ production by FliC(431–439)-specific CD4(+) T cells after stimulation in vivo. Moreover, after expression of the parental FliC(431–439) peptide or each APL in recombinant Listeria monocytogenes, only CD4(+) T cells stimulated with the wild-type FliC(431–439) peptide conferred significant protection against challenge with virulent Salmonella. These results reveal important and unanticipated roles for TCR stimulation in controlling pathogen-specific CD4(+) T cell proliferation, differentiation, and protective potency.